Pharmacokinetics of difloxacin in olive flounder Paralichthys olivaceus at two water temperatures. Issue 2 (6th June 2013) - Sun, M.; Li, J.; Gai, C. L.; Chang, Z. Q.; Li, J. T.; Zhao, F. Z.
<x xml:space="preserve">Abstract</x> In this study, the pharmacokinetics profiles of difloxacin in the olive flounder (Paralichthys olivaceus) were investigated following intravenous and oral administration (10 mg/kg BW) at 14 and 22 °C water temperatures. Plasma and tissue samples (muscle, liver, and kidney) were analyzed using an HPLC method. The results showed that the plasma concentration–time data for difloxacin were described commendably by two‐compartment open model at the two water temperatures. The absorption half‐life (t1/2ka) of difloxacin after oral administration were 2.08 and 1.10 h at 14 and 22 °C, respectively; whereas the elimination half‐life (t1/2β) was 4.41 and 2.38 h, respectively. The muscle concentration of 1.35 ± 0.19 μg/g was observed at 9 h at 14 °C, and 2.11 ± 0.33 μg/g at 6 h at 22 °C, respectively. For liver, the peak concentration of difloxacin 2.43 ± 0.30 μg/g occurred at 6 h at 14 °C, which was lower than the 3.34 ± 0.24 μg/g peak that occurred at 4 h at 22 °C. The calculated bioavailability of difloxacin was 68.07% at 22 °C, which was higher than the 53.43% calculated for 14 °C. After intravenous administration, the t1/2β were 4.79 and 2.81 h at 14 and 22 °C, respectively. The results indicate that the peak concentrations in muscle and liver at 14 °C are approximately half of those achieved at 22 °C. However, the Cmax in kidney at 14 and 22 °C were similar. The Vd values were 1.20 and 1.75 L/kg at 14 and 22 °C, respectively. These data indicated that both temperature and drug administration had significant effects on the elimination of difloxacin, and lower temperature or oral administration resulted in lower elimination.